Scelta linguistica e identità nella popolazione bilingue ucraina (Altre Modernità, 2022)
Since 1991, Ukraine’s independence has led to a (re)discovery of a national identity, which, in turn, spurred a renewed interest in the Ukrainian language as a peculiar trait of the new national community and prompted significant growth in its status and domains of use. At the same time, Russian was declared the language of a national minority. However, the 2001 census along with more recent surveys showed the existence of a considerably large group of native Russian speakers and noticed that the use of Russian extends beyond this specific community. This article contributes to research on the sociolinguistic situation of the Russian language, by presenting the main results of the field research I conducted in Ukraine in 2018. A quantitative and qualitative analysis of these data shows the deep complexity of the linguistic and cultural context of this country, as language choices appear to be closely intertwined with the problematic definition of one’s identity and with the difficulty in determining what it means to be Ukrainian.
Keywords: bilingualism; Ukraine; language and identity; language choice